Understanding 6th-century barbarian social organization and migration through paleogenomics - Carlos Eduardo G. Amorim (Nature Portfolio, 2018)
The Longobards invaded and conquered much of Italy after the fall of the Western Roman Empire. Here, the authors sequence and analyze ancient genomic DNA from 63 samples from two cemeteries associated with the Longobards and identify kinship networks and two distinct genetic and cultural groups in each.